1976
DOI: 10.1097/00000658-197603000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Management of Bacterial Endocarditis

Abstract: A total of 239 surgically treated patients with primary endocarditis were reviewed both from the literature and from our own experience. The age range was 10 to 74 years with a male to female ratio of 3:1. A wide variety of organisms was found. However, as a group, gram positive organisms predominate. The onset of congestive failure was the major indication for surgery. The aortic valve was predominantly involved with the mitral valve running a distant second. The hospital mortality rate was 20% and the late m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In our first patient, debridement of pulmonic valve vegetations extending from a pulmonic valve cusp was performed. This technique has been previously described (Laniardo et al, 1971;Parrott et al, 1976). Pulmonary insufficiency following excision of a leaflet or the pulmonic valve does not usually produce any significant functional impairment when pulmonary artery pressures are normal (Gilbert et al, 1960).…”
Section: Discussionmentioning
confidence: 99%
“…In our first patient, debridement of pulmonic valve vegetations extending from a pulmonic valve cusp was performed. This technique has been previously described (Laniardo et al, 1971;Parrott et al, 1976). Pulmonary insufficiency following excision of a leaflet or the pulmonic valve does not usually produce any significant functional impairment when pulmonary artery pressures are normal (Gilbert et al, 1960).…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to identify the causative organism in 37% of the patients, which was a higher rate than in other reports. [1][2][3][4][5][6]10,12 Failure to culture a causative organism may occur for several reasons, including inadequate microbiological techniques and infection with fastidious bacteria or nonbacterial microorganisms. However, the administration of antibiotics before taking blood cultures might have been the main reason.…”
Section: Causative Organismsmentioning
confidence: 99%
“…In the 1970s, Parrot et al, 2 Jung et al 3 and Boyd et al 4 each reported a mortality rate of approximately 30% after surgical treatment of infective endocarditis. However, development of better diagnostic tools, earlier surgical intervention, advances in operative techniques and myocardial protection, and more effective perioperative antibiotic therapy have gradually improved the results.…”
Section: Mortalitymentioning
confidence: 99%
“…The effectiveness of bactericidal antibiotics in curing most cases of IE contributed to the initial notion of delaying surgical valvular intervention in IE 6 . This approach was challenged, however, as a growing number of reports on significant valvular damage, HF and increased mortality accumulated 7,8 . Therefore, consensus recommendations were drawn regarding the need for early surgical interventions in certain high‐risk IE cases including haemodynamic instability, heart block, HF, systemic embolization and persistent infection 9 .…”
mentioning
confidence: 99%
“…6 This approach was challenged, however, as a growing number of reports on significant valvular damage, HF and increased mortality accumulated. 7,8 Therefore, consensus recommendations were drawn regarding the need for early surgical interventions in certain high-risk IE cases including haemodynamic instability, heart block, HF, systemic embolization and persistent infection. 9 Of these features, HF was repeatedly shown to represent both a common risk factor, but also a significant sign for early complications and increased mortality and was therefore suggested as an important marker for the need for early surgical In this issue of the Journal, Bohbot et al 11 explored the characteristics, management and outcomes of left-sided IE complicated by HF and described the effect of early surgical intervention on mortality rates in these patients.…”
mentioning
confidence: 99%